1998
DOI: 10.1136/bjo.82.4.410
|View full text |Cite
|
Sign up to set email alerts
|

Use of eye care services by people with diabetes: the Melbourne Visual Impairment Project

Abstract: Aim-The use of eye care services by people with and without diabetes was investigated in the Melbourne Visual Impairment Project (VIP), a population based study of eye disease in a representative sample of Melbourne residents 40 years of age and older. Methods-A comprehensive interview was employed to elicit information on history of diabetes, medication use, most recent visit to an ophthalmologist and optometrist, and basic demographic details. Presence and extent of diabetic retinopathy was determined by dil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(82 citation statements)
references
References 21 publications
5
74
1
2
Order By: Relevance
“…These findings reproduce the conditions of SUS patients in our region (6,7) and are in agreement with most studies conducted in different locations (5)(6)(7)(8)(9)(10)(11)(12)(13)(24)(25)(26)(27)(28)(29) , which show that longer disease duration and greater difficulty controlling the disease (requiring insulin use) are associated with more severe ocular manifestations.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These findings reproduce the conditions of SUS patients in our region (6,7) and are in agreement with most studies conducted in different locations (5)(6)(7)(8)(9)(10)(11)(12)(13)(24)(25)(26)(27)(28)(29) , which show that longer disease duration and greater difficulty controlling the disease (requiring insulin use) are associated with more severe ocular manifestations.…”
Section: Discussionsupporting
confidence: 81%
“…Most diabetic patients, with rare exceptions (4) , do not undergo preventive ophthalmic examination with the recommended frequency and they ignore the consequences of the disease and the importance of prevention (5)(6)(7)(8)(9)(10)(11)(12)(13) . The most efficient method for evaluating the population utilises non-mydriatic cameras and specialised image-processing centres (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) .…”
Section: Introductionmentioning
confidence: 99%
“…The rate of diabetic patients examined by ophthalmologists were two thirds, 61% and 42% in three different studies and examination by a neurologist was reported as 7% (15)(16)(17). In our study, examination rate by an ophthalmologist was 64.7% and neurologic examination had been performed in 25.7%.…”
Section: Comparison With Existing Literaturementioning
confidence: 83%
“…Apesar de já existirem evidências de que a educação de pacientes diabéticos e seus parentes constitui um ponto fundamental tanto para encorajar rastreamentos mais regulares para RD quanto na prevenção e tratamento da RD (14,(19)(20)(21)(22)(23) , a maioria dos pacientes na nossa amostra relata que nunca havia recebido alguma informação ou palestra sobre diabetes de algum profissional de saúde, bem como não haviam recebido algum tipo de material informativo sobre DM. Uma grande parte da nossa amostra também nunca havia participado de programas de educação sobre DM.…”
Section: Discussionunclassified